2014
DOI: 10.1159/000363334
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gender-Related Differences in Symptoms and Referral Patterns prior to Initial Diagnosis of Urothelial Carcinoma of the Bladder: A Prospective Cohort Study

Abstract: Objective: To analyze gender-specific differences regarding clinical symptoms, referral patterns and tumor biology prior to initial diagnosis of urothelial carcinoma of the bladder (UCB). Methods: A consecutive series of patients with an initial diagnosis of UCB was included. All patients completed a questionnaire on demographics, clinical symptoms and referral patterns. Results: In total, 68 patients (50 men, 18 women) with newly diagnosed UCB at admission for transurethral resection of bladder tumors were re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…Women were more often treated for urinary tract infection and were given symptomatic treatment without further clinical evaluation more frequently than men before being referred to an urologist [11]. Similar data have recently been reported by Aziz et al using the same questionnaire developed by Henning et al [11,12]. These data suggest that an unequal referral pattern might indeed be - at least partly - responsible for the higher tumour stages in women at initial diagnosis [10].…”
Section: Discussionmentioning
confidence: 56%
“…Women were more often treated for urinary tract infection and were given symptomatic treatment without further clinical evaluation more frequently than men before being referred to an urologist [11]. Similar data have recently been reported by Aziz et al using the same questionnaire developed by Henning et al [11,12]. These data suggest that an unequal referral pattern might indeed be - at least partly - responsible for the higher tumour stages in women at initial diagnosis [10].…”
Section: Discussionmentioning
confidence: 56%
“…Less than half of the women compared to 81% of the men directly consulted an urologist for haematuria [18]. These data suggest an unequal referral pattern that might be -at least partly -responsible for the higher tumour stages of women at initial diagnosis [2,[17][18][19]. Gender differences in perioperative complications following RC are also of interest and concern.…”
Section: Discussionmentioning
confidence: 94%
“…Two European studies based on health systems that allow for direct self-referral to a specialist Urology service found that 78 versus 55% [5] and 84.0 versus 66.7% [6] of men and women, respectively, self-referred. This raises the possibility of a gender difference not only in terms of appreciation of significance of symptoms but also different attitudes toward accessing specialist healthcare that is in contrast to the traditional view of men displaying more risk-taking behavior and an aversion to seeking medical attention.…”
Section: Are There Gender Differences In Referral Patterns?mentioning
confidence: 99%
“…Women are more likely to have urinalysis and culture sent and more likely to be diagnosed with a UTI (33.1 vs. 17.6%, p < 0.001) [11] (61.1 vs. 20.0, p = 0.005) [6]. Cohn et al [11 ]also found that women were more likely to receive 3 or more courses of antibiotics than male patients prior to their bladder cancer diagnosis (8.7 vs. 5.2%, p < 0.001).…”
Section: Are There Gender Differences In Referral Patterns?mentioning
confidence: 99%